Linguistic Accuracy in Investigation Reports: A Systematic Review through a Forensic Linguistics Approach in SARA-related Cases - Purawinangun, Ira Anisa; Iskandar, Ifan; Anwar, Miftahulkhairah (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Investigation Report (BAP) is a legal document that contains the results of the examination of witnesses, suspects, or experts in a legal case. The accuracy of language in BAP is a fundamental aspect because it can affect the interpretation of judges and legal decisions. Therefore, the purpose of this study is to identify the linguistic challenges that often arise in BAP as well as provide solutions based on forensic linguistic theory to improve the clarity and objectivity of the legal document. The methods used are a systematic review of relevant literature on forensic linguistics, linguistic analysis in legal documents, and the application of pragmatic, syntactic, and semantic theories in the case of SARA. The results of the study are expected to show that linguistic errors in BAP—both morphological, syntactic, semantic, and pragmatic—have the potential to cause confusion in the interpretation of legal facts and can affect the outcome of the decision. Therefore, the development of an appropriate language model in the BAP is very necessary to ensure justice, reduce bias, and improve the quality of legal communication in the judicial process.